Pengaruh Pemberian Teh Daun Kelor Terhadap Peningkatan Produksi ASI pada Ibu Nifas di Rejoagung Banyuwangi - Diah Ayu Ratna Sari; Desy Purnamasari; Erlin Novitasari (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Suboptimal breast milk production during postpartum is a reason for formula feeding, thus preventing exclusive breastfeeding targets. According to the WHO, the global coverage of exclusive breastfeeding should reach 68% by 2023. Non-pharmacological efforts can be implemented by administering moringa leaf tea, which contains flavonoids, phytosterols, alkaloids, saponins, and tannins, which function as lactogogues to stimulate the hormones prolactin and oxytocin. The purpose of this study was to determine the effect of administering moringa leaf tea to breastfeeding mothers at the Fitriatul Laili Rejoagung Banyuwangi TPMB in 2025 on their ability to increase breast milk production. This study involved 30 postpartum mothers: 15 in the intervention group and 15 in the control group. The study used a two-group quasi-experimental pretest-posttest design. Five grams of moringa leaf tea, 200 milliliters daily for seven days, was administered to the intervention group. The control group received normal postpartum care. The sampling method used was sequential sampling. Ten breast milk production indices were used as instruments. A t-test was used for data analysis. This study has been ethically reviewed. According to the findings, the average breast milk production in the intervention group increased from 5.87 to 8.87, while in the control group it increased from 6.00 to 6.60. The intervention group's averages differed from the control group by 3.00 and 0.6, respectively. The p-value was 0.000, indicating that tea made from moringa leaves can increase breast milk production. Therefore, this tea is recommended as a natural substitute for breast milk production.